Stewardship program for restricted use of antimicrobials in the elderly: a cohort study in a quaternary hospital in Brazil - Angélica Caroline FERREIRA; Thauane Pereira NUNES; Maria Eduarda MORET; José Marcos DOS SANTOS; Débora Bighinzoli SOUZA; Andrea D'avila FREITAS; Paulo Porto FURTADO; Marcia GARNICA; Julienne Martins ARAÚJO; Natalia Zambão DA SILVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: The stewardship strategy refers to a consistent practice to promoting responsible antimicrobial use. Optimizing the use of antibiotics is critical to mitigating adverse effects and combating bacterial resistance. The pillars of a stewardship program include: i) clinical pharmacist and infectologist with expertise; ii) educational measures for prescribers, nurses and pharmacists; iii) prophylaxis and therapeutic protocol; iv) monitoring of indicators. In this scenario of antimicrobial rational use, the older population are more susceptible to infection because immunocenescence and, therefore, greater use of antimicrobials is expected. Thus, the aim of the present study is to evaluate the prescription compliance of antimicrobial whose use is restricted in a hospitalized elderly population. Method: observational, controlled study in a Brazilian hospital, from January 2021 to January 2022. Based on the electrotonic antimicrobial form, the compliance of the prescriptions was evaluated. The definition used for elderly corresponded to individuals over 60 years old, according to the Brazilian Nation Principles for Older Persons, ordinance number 2528, of October 2006. Restricted drugs were considered: carbapenems, polymyxin, ceftazidime-avibactam, linezolid, tigecycline, ceftaroline, echinocandins and amphotericin. Results: A total of 1.688 requests for restricted use were received, of which 53% corresponded use in elderly group. Neutropenic fever was more common in young people and the inpatient unit was the sector with the highest percentage of antimicrobials. Furthermore, teicoplanin was the main drug that required intervention. Conclusion: Faced with the increase in bacterial resistance, the rational use of antimicrobials is extremely important, especially in older age group.